100 SCREENING FOR SLEEP DISTURBANCE AS PART OF THE COMPREHENSIVE GERIATRIC ASSESSMENT. (18th November 2021) - Mc Carthy, C E; O'Malley, K; Geoghegan, J; Mannion, E; Costello, M; Murphy, R; Reddin, C; Waters, R; O'Donnell, M; Robinson, S; Canavan, M
Abstract: Background: Sleep disturbance is common in the older patient, and has been associated with many common comorbidities, falls, impaired quality of life, and mortality. Sleep disturbance screening and management are important elements of the comprehensive geriatric assessment (CGA). There are few sleep disturbance assessment tools, however, that have been validated for use in older patients, or in those with cognitive impairment. We sought to review the assessment and management of sleep disturbance within a regional integrated care outreach programme (ICOP), where the RU-SATED tool had been used. Methods: From March–June'21 the notes of 30 consecutive patients, presenting to ICOP with cognitive complaints, were reviewed. Demographic and sleep disturbance data were collected, in addition to whether advice, treatment or further assessment for sleep disturbance was documented. Feedback from staff on the utility of the RU-SATED tool was also sought. Results: Of those reviewed, the mean age was 80.3 (SD = 7.8), and the mean Montreal Cognitive Assessment score (MOCA) was 17.7 (SD = 5.9). Where data was available, the mean RU-SATED score was 7.6 (SD = 1.9), and 42% were frail (n = 11). The most commonly endorsed sleep symptom was sleep onset latency/sleep maintenance issues (n = 16). RU-SATED score did not significantly predict age, MOCA or frailty (p > 0.1 for all). Advice, treatment or further assessment of sleep disturbance was offered to 23% of patients (n = 7), and this was not predicted by overall RU-SATED score or by individual question responses (p > 0.1 for all). Staff also stated that they found elements of the tool difficult to explain and interpret. Conclusion: Although the numbers are small, we have not found the RU-SATED tool to be helpful in guiding the management of sleep disturbance in our cohort. A more practical CGA tool is currently in development by the ICOP service.